DETECTION OF PATHOGENIC BACTERIA AND MIXEDINFECTIONS WITH YEASTS WHICH CAUSE VAGINITIS AND IT’SRELATIONSHIP WITH THE AGE IN IRAQI WOMEN - Mohamed, Bushra; AL. Thwani, Amina (Iraqi Journal of Science, 2024)
This study aims to isolate the bacterial pathogens and mixed infections withyeasts which cause vaginitis in Iraqi women and it’s relationship with the age .Theresult revealed that the bacterial pathogens which isolated from genital tractidentified as: Escherichia coli, Pseudomonas aeruginosa, Gardnerella viginals,Klebsiella oxytoca ,Staphylococcus aureus and Proteus mirabilis. The results ofbacterial susceptibility tests showed that all isolates were resistant to Cefalexin,Tetracycline, Streptomycin and Rifampicin, as well as, all isolates were sensitive toChloramphenicol, but these were different in sensitivity for other antibiotics. Theresults of mixed infection of bacteria with yeasts revealed that Candida albicanswas co-existing with S.aureus in 14 vaginal swabs, E.coli in 6 vaginal swabs andwith two swabs of each Proteus mirabilis and K.oxytoca, while no mixed infectionwas observed neither with P. aeruginosa nor with G. viginals and the results of therelationship of bacterial vaginitis with the age showed that incidence of infectionwas high among females age group( 40-67 years).